Perbandingan Model Two Stay-Two Stray dan Konvensional dalam Pembelajaran Bahasa Indonesia Di MA Darul Fath Bontolangkasa - Haerina; Fitrawahyudi; Irwan Fadli (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study is quantitative research with a comparative approach aimed at identifying differences in student learning outcomes between Grade X and Grade XI at MA Darul Fath Bontolangkasa, Pangkep Regency. The sample was selected using simple random sampling, consisting of students from the 2021/2022 academic year. Data were analyzed using SPSS version 26. The experimental class, which used the cooperative learning model type Two Stay – Two Stray, achieved an average score of 82.56. In contrast, the control class, which applied the conventional learning model, scored an average of 77.89. Based on the results of the t-test, the significance value obtained was 0.421 (≥ 0.05), indicating that there is a statistically significant difference in learning outcomes between the two classes. Therefore, the Two Stay – Two Stray model was found to be more effective in improving student performance in Indonesian language subjects, particularly in prose and scientific writing materials.